1998
DOI: 10.1086/515243
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Relevance of the Nonstructural 5A Gene Interferon Sensitivity Determining Region Is Different in Infections with Genotype 1b and 3a Isolates of Hepatitis C Virus

Abstract: Hepatitis C virus (HCV) RNA serum concentration, quasispecies complexity, and sequence and phylogenetic analysis of the nonstructural 5A gene (NS5A) interferon sensitivity determining region (ISDR) were determined in pretreatment serum samples from 47 patients with chronic hepatitis C (36 infected by HCV genotype 1b and 11 by 3a). Among HCV genotype 1b-infected patients, virus load was lower (P = .003) and the number of NS5A-ISDR amino acid changes was higher (P = .001) in long-term responders than in non-long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
86
2
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 7 publications
12
86
2
2
Order By: Relevance
“…Recent studies from other areas of Europe confirmed the correlation between NS5A mutations and interferon sensitivity showing the comparative frequency of the HCV-1b mutant types as seen in Japan. 26,27 The differences of patients' backgrounds or the virological diversity among various geographic areas should be considered, and further careful, comparative studies are needed to make these points clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies from other areas of Europe confirmed the correlation between NS5A mutations and interferon sensitivity showing the comparative frequency of the HCV-1b mutant types as seen in Japan. 26,27 The differences of patients' backgrounds or the virological diversity among various geographic areas should be considered, and further careful, comparative studies are needed to make these points clear.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies did not find any correlation between NS5A structures and interferon effect, 19-25 while other studies did. 26,27 In addition, in HCV genotype 1a, 21-23 2c, 23 or 3a, 19,23,27 no clear association has been found. Therefore, the investigation on NS5A in HCV-2 is also important for elucidating the significance of NS5A in interferon resistance.…”
mentioning
confidence: 98%
“…Mutation number in ISDR had no significant effect on response to IFN-based therapy in G1a [37,38] and G3a [36]. However, mutations in the region corresponding to the ISDR of G1b (2126-2228) was reported to be associated with outcome of therapy in HCV G2a, and more than two mutations in ISDR were associated with good response to PEG-IFN plus RBV [39].…”
Section: Amino Acid Substitutions In Ns5a and Response To Ifn-based Tmentioning
confidence: 86%
“…The sequence of ISDR was further examined in HCV G1a, G2 and G3a [36]. Mutation number in ISDR had no significant effect on response to IFN-based therapy in G1a [37,38] and G3a [36].…”
Section: Amino Acid Substitutions In Ns5a and Response To Ifn-based Tmentioning
confidence: 99%
“…Consequently, a lot of effort has been put into trying to identify specific sequences in the HCV viral quasispecies that may determine resistance or sensitivity to antiviral therapy. Unfortunately, results have been inconclusive (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) probably because IFN-a does not specifically target a particular HCV gene. IFN-a activity enhances host antiviral responses that, in turn, exert selection pressures on various viral genome regions.…”
Section: Introductionmentioning
confidence: 99%